Educational computer programs «rugbi-13» for perfection of educational-training process in Rugby League - Подоляка, О. Б.; Пасько, В. В. (Slobozhanskyi Herald of Science and Sport, 2011)
The author's on-line computer tutorial «Rugby-13» program is presented for a help specialists on Rugby League in organization and educational-training process control. The program is designed for all of age-dependent groups of sportsmen and contains the followings sections: educational, technical, tactical and physical preparation, game rubes and vocabulary of the special terms. The program is placed in the world network of Internet on the site of Ukrainian Federation Rugby League (www.rugby13.org.ua).